Equations of state for 1-D modelling of ram accelerator thrust in thermally choked propulsion mode. (13th September 2010) - Bengherbia, Tarek; Yao, Yufeng; Bauer, Pascal; Knowlen, Carl
A one-dimensional performance analysis code has been developed at the Laboratoire de Combustion et de Detonique to predict the thrust in the thermally choked ram accelerator propulsion mode. This code includes the real gas effect in steady state calculations and incorporates the following equations of state: ideal gas, Boltzmann, Percus-Yevick (PY) and Becker-Kistiakowsky-Wilson (BKW). The code was validated against key experimental data from representative experiments at the University of Washington 38-mm-bore facility. The predicted thrust and velocity agree well with experimental measurements. The present paper provides details about the algorithm of the calculation in the thermally choked propulsion mode.